A High-Speed and High-Sensitivity Photon-Counting Communication System Based on Multichannel SPAD Detection - Guanhua Wen; Jun Huang; Liang Zhang; Changkun Li; Tiancheng Wen; Jianyu Wang (IEEE Photonics Journal, 2021)
In order to achieve high-speed, high-sensitivity optical communication over long distances and high attenuation channels, we propose a photon-counting communication system based on the detection of multichannel single-photon avalanche diodes (SPADs). First, the ideal pulse position modulation (PPM) bit error rate (BER) expression for a multichannel detection system is derived, and then the effect of the detector's dead time is taken into account. The BER of the multichannel detection system was analyzed by means of a Monte Carlo simulation, after which we set up a four-channel receiving experimental verification system with a 1 × 4 fiber splitter and four single-photon counting modules (SPCMs). The simulation and experimental results demonstrated that the BER of the multichannel detection system could be greatly reduced and the communication speed substantially improved. Finally, a reliable photon-counting communication system with a rate of 50 Mbps and sensitivity of 4 photons/bit was developed using serially-concatenated pulse position modulation (SCPPM) technology.